Zespół zmęczenia, depresja oraz jakość życia u pacjentów ze stwardnieniem rozsianym - Halicka, Dorota; Tarasiuk, Joanna; Szczepański, Michał; Krajewska, Agata; Kułakowska, Alina (Pielęgniarstwo Neurologiczne i Neurochirurgiczne, 2017)
Introduction. Multiple sclerosis is a chronic disease of central nervous system of autoimmunological origin, in which next to an increased physical disability, neuropsychological disorders exist, that lead to significant decrease in patients’ quality of life. Aim. The aim of the study was the assessment of prevalence of fatigue syndrome and depression in patients with multiple sclerosis and their influence on functioning in physical, cognitive and psychosocial dimension as well as on the quality of life. Materials and Methods. 62 patients (37 females and 25 males) with relapsing-remitting subtype of multiple sclerosis and 15 patients with sciatica (9 females and 6 males) as the reference group were included in the study. Prevalence of fatigue syndrome and depression, as well as patients’ quality of life were assessed with use of Modified Fatigue Impact Scale (MFIS), Beck Depression Inventory (BDI) and a standardized instrument for use as a measure of health outcome EQ-5D. Results. Fatigue of moderate intensity was noticed in 45.16% (n=28) of patients with relapsing-remitting subtype of MS, when depression was apparent in 51.61% of patients (n=32), including mild depressive disorders in 33.8% of patients (n=21), moderate in 11.29% of patients and severe in 6.45% (n=4). The obtained results did not reach statistical significance when compared to results obtained in the reference group. Statistically significant dependence between the intensity of depression and influence of fatigue on functioning in psychosocial dimension was mainly observed in the group of patients with multiple sclerosis. Conclusions. Fatigue syndrome and depression occur in significant part of patients with relapsing-remitting subtype of multiple sclerosis, disturbing their functioning in psychosocial dimension and considerably decreasing their quality of life. Increase in fatigue in general dimension has a significantly positive correlation with exacerbation of depression in the group of patients with relapsing-remitting subtype of multiple sclerosis. (JNNN 2017;6(2):81–87)